2014
DOI: 10.1007/s00449-014-1328-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactins production by Bacillus amyloliquefaciens R3 and their antibacterial activity against multi-drug resistant pathogenic E. coli

Abstract: In this work, the anti-Escherichia coli activity of the bioactive substances produced by Bacillus amyloliquefaciens R3 was examined. A new and cheap medium for production of the anti-E. coli substances which contained 20.0 g L(-1) soybean powder, 20.0 g L(-1) wheat flour, pH 6.0 was developed. A crude surfactant concentration of 0.48 mg mL(-1) was obtained after 27 h of 10-L fermentation, and the diameter of the clear zone on the plate seeded with the pathogenic E. coli 2# was 23.3 mm. A preliminary characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Fermented soybean meal has also been shown to improve animal performance. A previous study performed using the spores of B. amyloliquefaciens to ferment whole soybean as a target dietary supplement for use in poultry feeds was able to increase growth rate and feed efficiency by 8% and 8.8%, respectively [ 54 ]. Also, this species of bacteria has been found to have anti-bacteria activity [ 55 ] and antioxidative activity [ 46 , 55 ], which may be able to improve growth performance for weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Fermented soybean meal has also been shown to improve animal performance. A previous study performed using the spores of B. amyloliquefaciens to ferment whole soybean as a target dietary supplement for use in poultry feeds was able to increase growth rate and feed efficiency by 8% and 8.8%, respectively [ 54 ]. Also, this species of bacteria has been found to have anti-bacteria activity [ 55 ] and antioxidative activity [ 46 , 55 ], which may be able to improve growth performance for weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have shown that the cyclic lipopeptides (CLPs) produced by Bacillus spp. have potent antimicrobial activity against antibiotic-resistant strains and can be generally divided into three main families: surfactin, fengycin, and iturin (Chi et al, 2015;Jemil et al, 2017;Perez et al, 2017;Piewngam et al, 2018). Due to their specific amphiphilic structure, CLPs primarily destroy target organisms by directly disrupting the integrity of the plasma membrane or cell wall in a detergent-like manner, and thus display a lower propensity to develop resistance than do conventional antibiotics (Banat et al, 2010;Mandal et al, 2013;Singh and Abraham, 2014;Patel et al, 2015;Ndlovu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the genus Bacillus has been widely used in aquaculture [ 12 , 13 ], and it may produce a variety of secondary metabolites with antibacterial and antifungal activities, including small peptides and proteins, polyketones, and lipopeptides [ 14 , 15 , 16 ]. For example, Bacillus licheniformis and B. flexus can effectively enhance the growth, digestive enzyme activities, innate immune enzyme activities, stress tolerance, and disease resistance of Litopenaeus vannamei [ 17 ].…”
Section: Introductionmentioning
confidence: 99%